Rational Engineers – Sensitive Philanthropists. About Selected Building. Projects and Their Authors in the Turn of the 19th and the 20th Centuries - Kiełb, Ewa (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
The article is dedicated to selected construction projects in Nałęczów in the second half of the 19th and the beginning of the 20th centuries and their authors: Jan Koszczyc-Witkiewicz, Edmund Judycki and Franciszek Bogusław Lilpop. At the same time, these completed projects in the form of public utility buildings were a testimony of charity mentioned engineers and architects adapted to the needs of the local community, mainly the poor. They were also the realization of positivistic connecting beliefs combining philanthropic ideas with a public benefit, but also an expression of social sensibility of the aforementioned authors who saw the need for charity also in the most famous Spa in the Kingdom of Poland under the Russian annexation.